Free human DNA attenuates the activity of antimicrobial peptides in atopic dermatitis. Issue 10 (16th July 2021) - Kopfnagel, Verena; Dreyer, Sylvia; Zeitvogel, Jana; Pieper, Dietmar H.; Buch, Anna; Sodeik, Beate; Rademacher, Franziska; Harder, Jürgen; Werfel, Thomas
Abstract: Background: The high susceptibility of AD patients to microbial skin infections has been attributed to a deficient antimicrobial peptide (AMP) expression, which is contradicted by a growing amount of recent studies clearly demonstrating that AMP expression is not impaired in lesional skin of AD patients. The reasons for the high susceptibility of AD patients to microbial infections are still unknown. Methods: The influence of self‐DNA on the antimicrobial activity of RNase 7, LL‐37, and hBD2 has been investigated using antibacterial and antiviral assays. The amount of self‐DNA on skin has been analyzed by skin rinsings and subsequent quantification using dsDNA assays. DNA source was identified by qPCR. Results: Complex formation of the AMPs with self‐DNA significantly impaired their antibacterial activity against Staphylococcus aureus and their antiviral activity against HSV ‐ 1 . The inhibition of the antibacterial activity was dependent on the DNA concentration but not on the length of the DNA molecules. Of note, we detected significant higher amounts of cell‐free self‐DNA in skin rinses taken from lesional AD skin compared to skin rinses from non‐lesional skin and from normal skin of healthy donors. Consequently, rinse solution from AD lesional skin prevented antibacterial activity of LL‐37. Conclusion: Our study indicates that extracellular self‐DNA is released in considerable amounts in AD skin lesions and AMP‐self‐DNA‐complex formation leads to a significant loss of antibacterial and antiviral activity in atopic dermatitis. Studies on strategies to reduce the amount of extracellular DNA in AD are needed to identify possible methods relevant in clinical settings. Abstract : AMP‐DNA complex formation impairs antimicrobial activities of AMPs. Inhibitory effect of DNA depends on the amount of DNA not on the length of the molecule. Analyses from skin rinses reveal a significantly higher amount of free self‐DNA in lesional AD skin compared to non‐lesional or healthy skin. Abbreviations: AD, atopic dermatitis; AMP, antimicrobial peptide